Innovative scoring system for statistical reasoning, literacy, and thinking (REaLITI) assessment instruments / Nurhasniza Idham Abu Hasan ... [et al.] - Abu Hasan, Nurhasniza Idham; Jamian, Nurul Husna; Ganggayah, Mogana Darshini; Md. Ghani, Nor Azura (2024)
Developing statistical abilities, including literacy, reasoning, and critical thinking, has become a crucial concern in statistical education. However, many students encounter challenges in mastering these abilities. A critical issue here is determining how to assess these statistical skills so that students can comprehend and excel in their statistics courses. To address this issue, the Statistical Reasoning, Literacy, and Thinking (REaLITI) Assessment Instrument was developed to assess these abilities. This paper outlines the development process of the REaLITI instrument scoring system assessment. This project aims to identify the measurement model that best captures the constructs of these skills while meeting good psychometric properties. The results indicate that the REaLITI instrument effectively measures statistical literacy, reasoning, and thinking with high-reliability scores. Furthermore, this instrument allows for students' performance to be categorized into groups such as "Poor and in need of attention," "Satisfactory, requiring some effort," or "Excellent in Statistics."